2017
DOI: 10.1007/s00246-017-1713-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of 22q11.2 Microdeletion on Cardiac Surgery Postoperative Outcome

Abstract: 22q11.2 microdeletion is the most common microdeletion in humans. The purpose of this study was to evaluate postoperative outcome in children with 22q11.2 microdeletion who had undergone complete surgical correction of a congenital heart defect. The study included 34 patients who underwent complete correction of conotruncal heart defects. Of these, 17 patients diagnosed with 22q11.2 microdeletion represent the investigated group. Another 17 patients without 22q11.2 microdeletion represent the control group. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
7
0
1
Order By: Relevance
“…The second main finding in this study was the presence of an inverse risk of death associated with 22q11.2 deletion syndrome despite having higher percentage of patients of Hispanic race and fewer patients with private insurance. Many researchers have examined the operative mortality in truncus arteriosus and some have found that 22q11.2 deletion syndrome does not necessarily increase surgical risk, 14‐16 while others reveal that 22q11.2 deletion is a significant risk factor for late mortality 17,18 . However, the results of our study are in agreement with the results of a study by Michielon et al 19 which found that 22q11.2 deletion syndrome was an inverse risk for death in patients with truncus arteriosus.…”
Section: Discussionsupporting
confidence: 90%
“…The second main finding in this study was the presence of an inverse risk of death associated with 22q11.2 deletion syndrome despite having higher percentage of patients of Hispanic race and fewer patients with private insurance. Many researchers have examined the operative mortality in truncus arteriosus and some have found that 22q11.2 deletion syndrome does not necessarily increase surgical risk, 14‐16 while others reveal that 22q11.2 deletion is a significant risk factor for late mortality 17,18 . However, the results of our study are in agreement with the results of a study by Michielon et al 19 which found that 22q11.2 deletion syndrome was an inverse risk for death in patients with truncus arteriosus.…”
Section: Discussionsupporting
confidence: 90%
“…In all three cohorts (tetralogy of Fallot, interrupted aortic arch, truncus arteriosus), these differences in outcome were not explained by the presence of major additional congenital anomalies, frequency of infections or use of nasogastric feeds, as one might have predicted. More recently, both Cuturilo et al () and Alsoufi et al () reported longer length of hospital stays, longer stays in the intensive care unit and/or longer use of mechanical ventilation, among other findings in the subset with a 22q11.2 deletion.…”
Section: The 22q112 Deletion Syndrome In the Chd Populationmentioning
confidence: 92%
“…feeds, as one might have predicted. More recently, bothCuturilo et al (2017) andAlsoufi et al (2017) reported longer length of hospital stays, longer stays in the intensive care unit and/or longer use of mechanical ventilation, among other findings in the subset with a 22q11.2 deletion.Thus, it is clear that cardiac patients with a 22q11.2 deletion at…”
mentioning
confidence: 95%
“…Para estudiar las complicaciones posoperatorias en corrección de cardiopatías congénitas Cuturilo et al [37] evaluaron pacientes con y sin MD22q11.2. La muestra se compuso por 17 casos y 17 controles, todos con cardiopatías similares entre ambos grupos.…”
Section: Complicaciones Posoperatorias En Cirugía Cardiovascularunclassified